Preparation method of high-entropy pyrochlore type catalytic material with diatom shell morphology
By constructing a high-entropy calcinedite-type catalytic material with diatom shell morphology, the problem of developing high-active and stable OER electrocatalysts in an acidic environment is solved, and efficient and economical catalytic performance is achieved, and the dependence of precious metals is avoided.
Patent Information
- Application Number
- CN202411792636.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-07
AI Technical Summary
The prior art is difficult to develop both highly active and stable oxidation (OER) electrocatalysts in acidic environments, especially under strong acidic conditions, and the stability and activity of the catalyst are difficult to take into account.
By constructing a high-entropy calcinedite-type catalytic material with diatom shell morphology, combining the high stability of the high-entropy material and the porous structure of the diatomaceous earth, a catalyst with high OER activity and acid resistance under acidic conditions was prepared.
Electrocatalytic properties with high stability and high activity under acidic conditions are achieved, reducing the production cost of catalysts and avoiding dependence on precious metals.
Smart Images

Figure CN119615272A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to a high-entropy pyrochlore-type (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 ) Preparation method of O7 catalytic material. Background Art
[0002] Diatomite is a natural hierarchical porous material with macropores, mesopores and micropores, and its reserves are also very considerable. Combined with its excellent hierarchical porous combination and high cost performance brought by its abundant reserves, diatomite is considered to be a very excellent catalytic carrier material, and has a wide range of applications in many heterogeneous catalytic fields including catalytic hydrogenation, Fenton catalysis, heavy oil conversion, catalytic hydration, catalytic esterification, etc.
[0003] At present, due to the energy storage needs of new energy industries such as photovoltaics and wind power, the conversion of excess electrical energy into the chemical energy of hydrogen for storage through water electrolysis has also attracted more and more attention. Among the many water electrolysis reactors, proton exchange membrane (PEM) water electrolysis hydrogen production technology is an emerging hydrogen production technology with the advantages of high current density and high energy efficiency. The PEM anode area is a strongly acidic environment, and the performance of the anode oxygen evolution reaction (OER) catalyst is the main factor limiting the performance of the PEM electrolyzer. Improving the activity and stability of the acidic OER catalyst is crucial to the development of the PEM electrolysis hydrogen production system. In an acidic environment, electrocatalytic oxygen evolution catalysts face challenges, including slow reaction kinetics caused by water molecule dissociation and multi-step reactions, and stability problems caused by dissolution / corrosion. Therefore, it is necessary to develop electrocatalysts that are both active and stable in acidic environments. Iridium oxide is currently the only commercially available OER electrocatalyst with acid stability, but the large-scale expansion of this precious metal requires more than 40 times the annual iridium production. Most transition metal-based materials can only carry out effective OER processes in alkaline electrolytes and are unstable under strongly acidic conditions. In this case, it is necessary to develop cheap catalysts with high OER activity and acid resistance. High entropy materials have higher stability due to high configurational entropy and more active sites exposed due to high disorder. Therefore, high entropy is an ideal strategy to achieve high stability and high activity of catalysts.
[0004] By constructing high-entropy materials into diatomite morphology, combining the high activity and high stability of high-entropy materials with the hierarchical porous structure of diatomite, it is expected to prepare OER electrocatalysts with better performance and more stability under acidic conditions. At the same time, there are few related reports. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-entropy pyrochlore-type catalytic material with diatom frustule morphology.
[0006] To solve the technical problem, the solution of the present invention is:
[0007] Provided is a method for preparing a high-entropy pyrochlore-type catalytic material having a diatom frustule morphology, comprising the following steps:
[0008] (1) Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, and NaNO3 are taken as solutes in an equal molar ratio; the solutes are added into a mixed solvent of propylene glycol, isohexanediol, n-butanol, and deionized water, and stirred until completely dissolved to obtain a solution 1;
[0009] (2) RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, and Cu(NO3)2 are taken as solutes in a molar ratio of 1:10:10:2:3:1; the solutes are added into a mixed solvent of triethanolamine, methanol, and acetone, and stirred until completely dissolved to obtain a second solution;
[0010] (3) adding diatomaceous earth to solution 2, with the mass ratio of diatomaceous earth to solution 2 being 0.05:0.95; after continuous stirring, a mixed solution 1 is obtained;
[0011] (4) Mixing liquid mixture 1 and solution 1 at a mass ratio of 1.5:1, adding all of solution 1 at once while stirring the liquid mixture 1; continuing to stir, obtaining liquid mixture 2;
[0012] (5) L-lysine and ascorbic acid are added to the mixed solution 2 at a mass ratio of 0.05:0.95, and the mass ratio of the total mass of L-lysine and ascorbic acid to the mixed solution 2 is 0.08:1; after continuous stirring for 20 to 40 minutes, hydrogen peroxide is added all at once, and continuous stirring is continued for another 20 to 40 minutes to obtain a mixed solution 3; the hydrogen peroxide accounts for 4% of the total mass of the mixed solution 3;
[0013] (6) Adding NaOH to the mixed solution 3, the mass ratio of NaOH to the mixed solution 3 is 0.05:0.95; stirring is continued for 1 to 3 hours to obtain a mixed solution 5;
[0014] (7) Adding the mixed solution 5 into a water-heated kettle with stirring, and then adding diatomaceous earth accounting for 1% by weight of the mixed solution 5, and stirring;
[0015] (8) Seal the hydrothermal autoclave while stirring, then heat to 90° C. and keep warm for 1 to 3 hours; then heat to 155° C. and keep warm for 1 to 3 hours; then heat to 190° C. and keep warm for 12 to 24 hours; stop heating, and cool to room temperature to obtain a mixture;
[0016] (9) taking the mixture 1 out of the hydrothermal kettle, filtering, washing, and drying to obtain a powder 1;
[0017] (10) taking a 1:10 mass ratio of the powder and a 0.5 wt % aqueous solution of gluconic acid, adding the two into a hydrothermal kettle with stirring, and stirring;
[0018] (11) Seal the hydrothermal reactor while stirring, raise the temperature to 240° C., and keep the temperature for 4 to 6 hours; stop heating, and cool to room temperature to obtain a mixture 2;
[0019] (12) taking the mixture 2 out of the hydrothermal reactor, filtering, washing, and drying to obtain powder 2;
[0020] (13) placing the powder obtained in step (12) in a tube furnace, heating it to 550° C., keeping it warm for 8 to 16 hours, and cooling it naturally to room temperature to obtain a high entropy pyrochlore-type catalytic material with diatom frustule morphology, the molecular expression of which is (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7.
[0021] As a preferred embodiment of the present invention, in the first solution, the mass ratio of the total mass of the solute to the mass ratio of the solvent is 7.5%; in the second solution, the mass ratio of the total mass of the solute to the mass ratio of the solvent is 13%.
[0022] As a preferred embodiment of the present invention, in the mixed solvent in step (1), the mass ratio of propylene glycol, isohexanediol, n-butanol and deionized water is 2:2:3:1.
[0023] As a preferred embodiment of the present invention, in the mixed solvent in step (2), the mass ratio of triethanolamine, methanol and acetone is 1:3:4.
[0024] As a preferred embodiment of the present invention, in the step (3), the stirring time is 1 to 3 hours.
[0025] As a preferred embodiment of the present invention, after adding solution 1 to mixed solution 1 in step (4), stirring is continued for 2 to 6 hours.
[0026] As a preferred embodiment of the present invention, in the step (7), the stirring rate is maintained at 300 rpm and the stirring is performed for 10 to 20 minutes.
[0027] As a preferred embodiment of the present invention, in the step (9), the product is washed three times with anhydrous ethanol and then dried; the drying temperature is 60° C. and the drying time is 24 hours.
[0028] As a preferred embodiment of the present invention, in the step (10), the stirring rate is maintained at 300 rpm and the stirring is carried out for 10 to 20 minutes.
[0029] As a preferred embodiment of the present invention, in the step (12), the product is washed three times with deionized water and then dried; the drying temperature is 80° C. and the drying time is 24 hours.
[0030] Description of the invention principle:
[0031] The present invention constructs a high entropy catalytic material with a diatom shell biological structure, fully utilizes the advantages of the high entropy material and the diatomite biological structure, and obtains a highly stable and highly active catalytic material suitable for electrocatalytic oxygen evolution under acidic conditions.
[0032] 1. Compared with conventional catalytic materials, high-entropy catalytic materials have better structural and chemical stability due to the principle of entropy stabilization. At the same time, due to the structural distortion brought about by high entropy, the catalytic material can have more active sites. The biological structure of diatom shells has hierarchical porous characteristics and is very conducive to the mass transfer process in the catalytic process of chemical reactions. Therefore, the catalytic material prepared in this application has better stability and higher activity.
[0033] 2. The present invention increases the ideal mixing entropy by increasing the types of elements in the compound, so as to prepare high-performance materials by utilizing the "cocktail effect" brought by the entropy increase. However, for different material systems and the performance to be improved, the ideal mixing entropy required to be increased (i.e., the types and quantities of the elements used) has a threshold value, and there is no unified standard. It is necessary to optimize it for different material systems by combining theory and experiment. The introduction of Na and Bi at the A position of pyrochlore, combined with the high entropy of the A position, can effectively modulate the electronic structure of the lanthanide elements at the A position of pyrochlore, so that the originally localized f orbital of the lanthanide elements at the A position of pyrochlore is further expanded, thereby promoting the participation of the A position of pyrochlore in the electrochemical reaction process and increasing the catalytic activity; in addition, the ionic radius of Y and Sc elements is also smaller than that of La, which is conducive to shrinking the size of the tetrahedron and further improving the orbital expansibility. At the B site of pyrochlore, the silicon element is creatively introduced, and the sp3 hybridized electronic configuration of the silicon element is utilized, which is conducive to breaking the octahedral configuration of the conventional B site. On the one hand, the octahedral structure of the original B site is greatly distorted, exposing more active sites, and on the other hand, other metal elements at the B site are modulated to have a more expanded d orbital. The introduction of Ag and Cu elements at the B position of pyrochlore can improve the conductivity of the material, which is beneficial to the improvement of the electrocatalytic performance.
[0034] 3. The present invention achieves the purpose of regulating structure and composition by mixing a variety of alcohol reagents so that the mixed solvent has the best solubility parameter and adjusts the ion product constant of the precursor metal salt in the solution.
[0035] 4. L-lysine and ascorbic acid have the ability to form complexes with metal oxide ions. The addition of L-lysine and ascorbic acid in the preparation process of the present invention can effectively adjust the deposition and reaction rate of each element, which is conducive to forming a precursor with more uniform element mixing; hydrogen peroxide has the effect of destroying metal oxygen bridging polymerization, which is conducive to breaking the bridging of a single metal oxide during the formation process, thereby making the element distribution in the obtained precursor more uniform. NaOH provides anions for the formation of the precursor; and the addition of gluconic acid is conducive to further microstructural optimization of the precursor before calcination, that is, through another dissolution-nucleation process, the uniformity of element distribution is further improved.
[0036] 5. The present invention provides a precursor with highly uniform element distribution for the subsequent formation of a high-entropy pyrochlore structure by multiple hydrothermal processes to improve the uniformity of element distribution.
[0037] 6. The pyrochlore structure itself has a high tolerance to acidic conditions. The present invention further improves the stability of pyrochlore under acidic conditions through the stabilization effect brought about by high entropy.
[0038] 7. The present invention makes full use of the hierarchical porous characteristics and orderly arrangement of pores in the shell-like biological particle structure in diatomite, which is beneficial to the mass transfer process in the chemical reaction catalysis process.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention optimizes the metal ion coordination process. By adjusting the metal ion complexes in the precursor solution to make the dissociation degrees of the metal ions similar, the pyrochlore A-site metal ions and B-site metal ions with large electronegativity differences have better synergy in the subsequent nucleation and crystallization processes, thereby improving the uniformity of the final product and reducing the formation temperature of the pyrochlore phase.
[0041] 2. The present invention reduces the formation temperature of pyrochlore through secondary hydrothermal reconstruction crystallization; therefore, compared with the prior art, it can save the production cost of catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is an electron microscope photograph of the high-entropy pyrochlore-type catalytic material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0044] In the following examples, Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, NaNO3, NaOH, RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, Cu(NO3)2 are all powdered solids. Glycerol, isohexanediol, n-butanol, triethanolamine, methanol, acetone, hydrogen peroxide, gluconic acid, L-lysine and ascorbic acid are all commercial reagents.
[0045] Part I: Examples of the implementation of the present invention
[0046] Example 1
[0047] (1) Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, and NaNO3 are taken as solutes in an equal molar ratio; the solutes are added into a mixed solvent of propylene glycol, isohexanediol, n-butanol, and deionized water in a mass ratio of 2:2:3:1, the mass ratio of the total mass of the solute to the mass of the solvent is 7.5%, and the solution is obtained after stirring until it is completely dissolved;
[0048] (2) RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, and Cu(NO3)2 were taken as solutes in a molar ratio of 1:10:10:2:3:1; the solutes were added into a mixed solvent of triethanolamine, methanol, and acetone in a mass ratio of 1:3:4, the total mass ratio of the solute to the solvent being 13%, and the solution was obtained by stirring until the solutes were completely dissolved;
[0049] (3) Add diatomaceous earth to solution 2 and continue stirring for 1 hour to obtain a mixed solution 1, wherein the mass ratio of diatomaceous earth to solution 2 is 0.05:0.95.
[0050] (4) Mixed solution 1 is continuously stirred, and during the stirring process, all solution 1 is added at once, and stirred for another 2 hours to obtain mixed solution 2. The mass ratio of mixed solution 1 to solution 1 is 1.5:1.
[0051] (5) adding L-lysine and ascorbic acid to the mixed solution 2, wherein the mass ratio of L-lysine to ascorbic acid is 0.05:0.95, and the mass ratio of the total mass of L-lysine and ascorbic acid to the mixed solution 2 is 0.08:1, and stirring is continued for 20 minutes; and once again, hydrogen peroxide accounting for 4% of the total mass is added in one go, and stirring is continued for another 20 minutes to obtain a mixed solution 3;
[0052] (6) Adding NaOH to the mixed solution 3, the mass ratio of NaOH to the mixed solution 3 is 0.05:0.95, and stirring is continued for 1 hour to obtain the mixed solution 5;
[0053] (7) Add the mixed solution 5 into a hydrothermal kettle with stirring, then add diatomaceous earth accounting for 1% of the mass of the mixed solution, start stirring, maintain the stirring rate at 300 rpm, and stir for 10 minutes;
[0054] (8) Keep stirring, seal the hydrothermal kettle, raise the temperature to 90°C, and keep it warm for 1 hour; then raise the temperature to 155°C, and keep it warm for 1 hour; then raise the temperature to 190°C, and keep it warm for 12 hours; stop heating, and cool to room temperature to obtain a mixture;
[0055] (9) The mixture 1 is taken out from the hydrothermal autoclave, filtered and washed three times with anhydrous ethanol, and dried to obtain a powder 1; the drying temperature is 60° C. and the drying time is 24 hours;
[0056] (10) Mixing powder 1 with a 0.5 wt % gluconic acid aqueous solution, adding the mixture to a hydrothermal kettle with stirring, turning on the stirring, maintaining the stirring rate at 300 rpm, stirring for 10 minutes, the mass ratio of powder 1 to the gluconic acid aqueous solution being 1:10;
[0057] (11) Keep stirring, seal the hydrothermal kettle, raise the temperature to 240° C., and keep the temperature for 4 hours; stop heating, and cool to room temperature to obtain a mixture 2;
[0058] (12) The mixture 2 is taken out from the hydrothermal autoclave, filtered and washed three times with deionized water, and dried to obtain the powder 2; the drying temperature is 80° C. and the drying time is 24 hours;
[0059] (13) placing the powder obtained in step (12) in a tube furnace, heating it to 550° C., keeping it at that temperature for 8 hours, and naturally cooling it to room temperature to obtain a high-entropy pyrochlore-type catalytic material with a diatom frustule morphology.
[0060] The molecular expression of the catalytic material was confirmed by inductively coupled plasma mass spectrometry (ICP-MS): 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7.
[0061] Take 5 mg of high entropy pyrochlore (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7 catalyst was added to 500 μl of ethanol, and then 50 μl of Nafion solution was added, and ultrasonicated for 1 hour to prepare a dispersion. 50 μl of the dispersion was dropped on 5 mm*5 mm carbon paper, and dried to prepare a working electrode. The catalyst loading was 1 mg / cm 2 A three-electrode electrolytic cell was used, with a 1*1cm platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a 0.5M H2SO4 aqueous solution as the electrolyte, and the polarization curve was tested in the range of 0 to 1V.
[0062] After testing, it reaches 10m A / cm 2 The potential required for the current density is 220 mV.
[0063] Example 2
[0064] (1) Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, and NaNO3 are taken as solutes in an equal molar ratio; the solutes are added into a mixed solvent of propylene glycol, isohexanediol, n-butanol, and deionized water in a mass ratio of 2:2:3:1, the mass ratio of the total mass of the solute to the mass of the solvent is 7.5%, and the solution is obtained after stirring until it is completely dissolved;
[0065] (2) RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, and Cu(NO3)2 were taken as solutes in a molar ratio of 1:10:10:2:3:1; the solutes were added into a mixed solvent of triethanolamine, methanol, and acetone in a mass ratio of 1:3:4, the total mass ratio of the solute to the solvent being 13%, and the solution was obtained by stirring until the solutes were completely dissolved;
[0066] (3) Add diatomaceous earth to solution 2 and continue stirring for 3 hours to obtain a mixed solution 1, wherein the mass ratio of diatomaceous earth to solution 2 is 0.05:0.95.
[0067] (4) Mixed solution 1 is continuously stirred, and during the stirring process, all solution 1 is added at once, and stirred for another 6 hours to obtain mixed solution 2. The mass ratio of mixed solution 1 to solution 1 is 1.5:1.
[0068] (5) adding L-lysine and ascorbic acid to the mixed solution 2, wherein the mass ratio of L-lysine to ascorbic acid is 0.05:0.95, and the mass ratio of the total mass of L-lysine and ascorbic acid to the mixed solution 2 is 0.08:1, and stirring is continued for 40 minutes; and once again, hydrogen peroxide accounting for 4% of the total mass is added in one go, and stirring is continued for another 40 minutes to obtain a mixed solution 3;
[0069] (6) Adding NaOH to the mixed solution 3, the mass ratio of NaOH to the mixed solution 3 is 0.05:0.95, and stirring is continued for 3 hours to obtain the mixed solution 5;
[0070] (7) Add the mixed solution 5 into a stirred hydrothermal kettle, add diatomaceous earth accounting for 1% of the mass of the mixed solution, start stirring, maintain the stirring rate at 300 rpm, and stir for 20 minutes;
[0071] (8) Keep stirring, seal the hydrothermal kettle, raise the temperature to 90° C., and keep it warm for 3 hours; then raise the temperature to 155° C., and keep it warm for 3 hours; then raise the temperature to 190° C., and keep it warm for 24 hours; stop heating, and cool to room temperature to obtain a mixture 1;
[0072] (9) The mixture 1 is taken out from the hydrothermal autoclave, filtered and washed three times with anhydrous ethanol, and dried to obtain a powder 1; the drying temperature is 60° C. and the drying time is 24 hours;
[0073] (10) Mixing powder 1 with a 0.5 wt % gluconic acid aqueous solution, adding the mixture to a hydrothermal kettle with stirring, turning on stirring, maintaining the stirring rate at 300 rpm, stirring for 20 minutes, wherein the mass ratio of powder 1 to the gluconic acid aqueous solution is 1:10;
[0074] (11) Keep stirring, seal the hydrothermal autoclave, raise the temperature to 240° C., and keep the temperature for 6 hours; stop heating, and cool to room temperature to obtain a mixture 2;
[0075] (12) The mixture 2 is taken out from the hydrothermal autoclave, filtered and washed three times with deionized water, and dried to obtain the powder 2; the drying temperature is 80° C. and the drying time is 24 hours;
[0076] (13) placing the powder obtained in step (12) in a tube furnace, heating it to 550° C., keeping it at that temperature for 16 hours, and naturally cooling it to room temperature to obtain a high-entropy pyrochlore-type catalytic material with a diatom frustule morphology.
[0077] The molecular expression of the catalytic material was confirmed by inductively coupled plasma mass spectrometry (ICP-MS): 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7.
[0078] Take 5 mg of high entropy pyrochlore (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7 catalyst was added to 500 μl of ethanol, and then 50 μl of Nafion solution was added, and ultrasonicated for 1 hour to prepare a dispersion. 50 μl of the dispersion was dropped on 5 mm*5 mm carbon paper, and dried to prepare a working electrode. The catalyst loading was 1 mg / cm 2A three-electrode electrolytic cell was used, with a 1*1cm platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a 0.5M H2SO4 aqueous solution as the electrolyte, and the polarization curve was tested in the range of 0 to 1V.
[0079] After testing, it reaches 10m A / cm 2 The potential required for the current density is 181 mV.
[0080] Example 3
[0081] (1) Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, and NaNO3 are taken as solutes in an equal molar ratio; the solutes are added into a mixed solvent of propylene glycol, isohexanediol, n-butanol, and deionized water in a mass ratio of 2:2:3:1, the mass ratio of the total mass of the solute to the mass of the solvent is 7.5%, and the solution is obtained after stirring until it is completely dissolved;
[0082] (2) RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, and Cu(NO3)2 were taken as solutes in a molar ratio of 1:10:10:2:3:1; the solutes were added into a mixed solvent of triethanolamine, methanol, and acetone in a mass ratio of 1:3:4, the total mass ratio of the solute to the solvent being 13%, and the solution was obtained by stirring until the solutes were completely dissolved;
[0083] (3) Add diatomaceous earth to solution 2 and continue stirring for 2 hours to obtain a mixed solution 1, wherein the mass ratio of diatomaceous earth to solution 2 is 0.05:0.95.
[0084] (4) Mixed solution 1 is continuously stirred, and during the stirring process, all solution 1 is added at once, and stirred for another 4 hours to obtain mixed solution 2. The mass ratio of mixed solution 1 to solution 1 is 1.5:1.
[0085] (5) adding L-lysine and ascorbic acid to the mixed solution 2, wherein the mass ratio of L-lysine to ascorbic acid is 0.05:0.95, and the mass ratio of the total mass of L-lysine and ascorbic acid to the mixed solution 2 is 0.08:1, and stirring is continued for 30 minutes; and once again, hydrogen peroxide accounting for 4% of the total mass is added in one go, and stirring is continued for another 30 minutes to obtain a mixed solution 3;
[0086] (6) Adding NaOH to the mixed solution 3, the mass ratio of NaOH to the mixed solution 3 is 0.05:0.95, and stirring is continued for 2 hours to obtain the mixed solution 5;
[0087] (7) Add the mixed solution 5 into a stirred hydrothermal kettle, add diatomaceous earth accounting for 1% of the mass of the mixed solution, start stirring, maintain the stirring rate at 300 rpm, and stir for 15 minutes;
[0088] (8) Keep stirring, seal the hydrothermal kettle, raise the temperature to 90°C, and keep it warm for 2 hours; then raise the temperature to 155°C, and keep it warm for 2 hours; then raise the temperature to 190°C, and keep it warm for 18 hours; stop heating, and cool to room temperature to obtain a mixture;
[0089] (9) The mixture 1 is taken out from the hydrothermal autoclave, filtered and washed three times with anhydrous ethanol, and dried to obtain a powder 1; the drying temperature is 60° C. and the drying time is 24 hours;
[0090] (10) Mixing powder 1 with a 0.5 wt % gluconic acid aqueous solution, adding the mixture to a hydrothermal kettle with stirring, turning on the stirring, maintaining the stirring rate at 300 rpm, stirring for 15 minutes, the mass ratio of powder 1 to the gluconic acid aqueous solution being 1:10;
[0091] (11) Keep stirring, seal the hydrothermal autoclave, raise the temperature to 240° C., and keep the temperature for 5 hours; stop heating, and cool to room temperature to obtain a mixture 2;
[0092] (12) The mixture 2 is taken out from the hydrothermal autoclave, filtered and washed three times with deionized water, and dried to obtain the powder 2; the drying temperature is 80° C. and the drying time is 24 hours;
[0093] (13) placing the powder obtained in step (12) in a tube furnace, heating it to 550° C., keeping it warm for 12 hours, and naturally cooling it to room temperature to obtain a high-entropy pyrochlore-type catalytic material with a diatom frustule morphology.
[0094] The molecular expression of the catalytic material was confirmed by inductively coupled plasma mass spectrometry (ICP-MS): 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7.
[0095] Take 5 mg of high entropy pyrochlore (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu0.2 ,Ag 0.1 )O7 catalyst was added to 500 μl of ethanol, and then 50 μl of Nafion solution was added, and ultrasonicated for 1 hour to prepare a dispersion. 50 μl of the dispersion was dropped on 5 mm*5 mm carbon paper, and dried to prepare a working electrode. The catalyst loading was 1 mg / cm 2 A three-electrode electrolytic cell was used, with a 1*1cm platinum electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a 0.5M H2SO4 aqueous solution as the electrolyte, and the polarization curve was tested in the range of 0 to 1V.
[0096] After testing, it reaches 10m A / cm 2 The potential required for the current density is 197 mV.
[0097] Through electron microscopic observation, the elements of the materials obtained in Examples 1-3 above are the same in proportion, and all have the macroscopic structure of diatomaceous earth. Figure 1 The electron microscope photo of the product obtained in Example 1 is shown in Figure 2, and it can be seen that the product particles basically retain the original shell-like morphology of diatomite. Due to different control parameters in the preparation process of Examples 1-3, there will be slight performance differences due to reasons such as grain size and crystalline pyrochlore phase content, resulting in different electrocatalytic properties.
[0098] The second part is different from the comparative example of the present invention
[0099] Comparative Example 1.1
[0100] In Comparative Example 1.1, the preparation process of the catalytic material is the same as that of Example 1, and the only difference is the difference in the added components; relative to the product of Example 1, the product of Comparative Example 1.1 lacks the Na element accordingly.
[0101] Comparative Example 1.2
[0102] In Comparative Example 1.2, the preparation process of the catalytic material is the same as that of Example 1, and the only difference is the difference in the added components; relative to the product of Example 1, the product of Comparative Example 1.2 lacks Na and Bi elements accordingly.
[0103] Comparative Example 1.3
[0104] In Comparative Example 1.2, the preparation process of the catalytic material is the same as that of Example 1, and the only difference is the difference in the added components; relative to the product of Example 1, the product of Comparative Example 1.3 lacks Y and Sc elements accordingly.
[0105] Comparative Example 1.4
[0106] In Comparative Example 1.2, the preparation process of the catalytic material is the same as that of Example 1, and the only difference is the difference in the added components; relative to the product of Example 1, the product of Comparative Example 1.4 lacks the Si element accordingly.
[0107] Comparative Example 1.5
[0108] In Comparative Example 1.2, the preparation process of the catalytic material is the same as that of Example 1, and the only difference is the difference in the added components; relative to the product of Example 1, the product of Comparative Example 1.5 lacks Ag and Cu elements accordingly.
[0109] The same test method as in the embodiment of the present invention was used for the above five comparative examples, and the 2 The overpotential value required for the current density is used as a comparison object.
[0110] For ease of reading, the product formula and overpotential values of each comparative example are listed in the form of an appendix below.
[0111]
[0112] From the test data of comparative examples 1.1-1.5d, it can be seen that the catalytic materials of these five comparative examples have a high conductivity when the catalytic conductivity reaches 10 mA / cm 2 The overpotential of the overpotential value required for the current density is significantly higher than that of the product of the present invention. It can be seen that reducing the number of elements on the basis of the product of the present invention will lead to the deterioration of the final performance of the product.
[0113] Comparative Example 2
[0114] Referring to the patent document "Preparation of bifunctional catalyst diatomite confined cobalt-platinum-based composite materials and their application in electrocatalytic oxygen reduction and oxygen evolution reactions" (CN107342425 A), diatomite (DTM) confined cobalt-platinum-based composite electrode materials were prepared using diatomite, CoCl2·6H2O and H2PtCl6·6H2O as main raw materials.
[0115] Then, referring to the operation described in Example 1, the electrode material was processed into a working electrode and used to build a three-electrode electrolytic cell, and the polarization curve was tested to reach 10 mA / cm 2 The potential required for the current density is 396 mV.
[0116] Comparative Example 3
[0117] With reference to the records in the journal article "Study on the Performance of Catalytic Hydrogen Production by Diatomaceous Earth-Loaded Metal Catalysts", diatomaceous earth and cobalt nitrate were used as main raw materials to prepare diatomaceous earth loaded with metal cobalt and form electrode materials.
[0118] Then, referring to the operation described in Example 1, the electrode material was processed into a working electrode and used to build a three-electrode electrolytic cell, and the polarization curve was tested to reach 10 mA / cm 2 The potential required for the current density is 377 mV.
[0119] Comparative Example 4
[0120] Referring to the patent document "A catalyst and its preparation method" (CN115970688A), a crystalline composite of IrO2 and pyrochlore La2Ir2O7 was prepared to make an electrode material.
[0121] Then, referring to the operation described in Example 1, the electrode material was processed into a working electrode and used to build a three-electrode electrolytic cell, and the polarization curve was tested to reach 10 mA / cm 2 The potential required for the current density is 267 mV.
[0122] Comparative Example 5
[0123] With reference to the journal article “Mitigation of RuO6 octahedron distortion by enhanced A-siteelectronegativity in pyrochlore for acidic water oxidation”, pyrochlore Ho2Ru2O7 electrode material was prepared.
[0124] Then, referring to the operation described in Example 1, the electrode material was processed into a working electrode and used to build a three-electrode electrolytic cell, and the polarization curve was tested to reach 10 mA / cm 2 The potential required for the current density is 255 mV.
[0125] It can be seen from the test data of Comparative Examples 2-5 that the catalytic material obtained by the preparation method of the present invention has better electrocatalytic performance under acidic conditions than the catalyst prepared by the prior art.
[0126] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a high-entropy pyrochlore-type catalytic material having a diatom frustule morphology, characterized in that: The following steps are involved: (1) Y(NO3)3, La(NO3)3, AgNO3, Sc(NO3)3, Bi(NO3)3, and NaNO3 are taken as solutes in an equal molar ratio; the solutes are added into a mixed solvent of propylene glycol, isohexanediol, n-butanol, and deionized water, and stirred until completely dissolved to obtain a solution 1; (2) RuCl3, SnCl4, Co(NO3)2, IrCl3, AgNO3, and Cu(NO3)2 are taken as solutes in a molar ratio of 1:10:10:2:3:1; the solutes are added into a mixed solvent of triethanolamine, methanol, and acetone, and stirred until completely dissolved to obtain a second solution; (3) adding diatomaceous earth to solution 2, with the mass ratio of diatomaceous earth to solution 2 being 0.05:0.95; after continuous stirring, a mixed solution 1 is obtained; (4) Mixing liquid mixture 1 and solution 1 at a mass ratio of 1.5:1, adding all of solution 1 at once while stirring the liquid mixture 1; continuing to stir, obtaining liquid mixture 2; (5) L-lysine and ascorbic acid are added to the mixed solution 2 at a mass ratio of 0.05:0.95, and the mass ratio of the total mass of L-lysine and ascorbic acid to the mixed solution 2 is 0.08:1; after continuous stirring for 20 to 40 minutes, hydrogen peroxide is added all at once, and continuous stirring is continued for another 20 to 40 minutes to obtain a mixed solution 3; the hydrogen peroxide accounts for 4% of the total mass of the mixed solution 3; (6) Adding NaOH to the mixed solution 3, the mass ratio of NaOH to the mixed solution 3 is 0.05:0.95; stirring is continued for 1 to 3 hours to obtain a mixed solution 5; (7) Adding the mixed solution 5 into a water-heated kettle with stirring, and then adding diatomaceous earth accounting for 1% by weight of the mixed solution 5, and stirring; (8) Seal the hydrothermal autoclave while stirring, then heat to 90° C. and keep warm for 1 to 3 hours; then heat to 155° C. and keep warm for 1 to 3 hours; then heat to 190° C. and keep warm for 12 to 24 hours; stop heating, and cool to room temperature to obtain a mixture; (9) taking the mixture 1 out of the hydrothermal kettle, filtering, washing, and drying to obtain a powder 1; (10) taking a 1:10 mass ratio of the powder and a 0.5 wt % aqueous solution of gluconic acid, adding the two into a hydrothermal kettle with stirring, and stirring; (11) Seal the hydrothermal reactor while stirring, raise the temperature to 240° C., and keep the temperature for 4 to 6 hours; stop heating, and cool to room temperature to obtain a mixture 2; (12) taking the mixture 2 out of the hydrothermal reactor, filtering, washing, and drying to obtain powder 2; (13) placing the powder obtained in step (12) in a tube furnace, heating it to 550° C., keeping it warm for 8 to 16 hours, and cooling it naturally to room temperature to obtain a high entropy pyrochlore-type catalytic material with diatom frustule morphology, the molecular expression of which is (Y 0.4 ,La 0.4 ,Bi 0.4 ,Na 0.4 ,Sc 0.4 )(Ru 0.1 ,Si 0.1 ,Sn 0.6 ,Co 0.7 ,Ir 0.2 ,Cu 0.2 ,Ag 0.1 )O7.
2. The method according to claim 1, characterized in that In the first solution, the mass ratio of the total mass of the solute to the mass of the solvent is 7.5%; in the second solution, the mass ratio of the total mass of the solute to the mass of the solvent is 13%.
3. The method according to claim 1, characterized in that In the mixed solvent in step (1), the mass ratio of propylene glycol, isohexanediol, n-butanol and deionized water is 2:2:3:
1.
4. The method according to claim 1, characterized in that: In the mixed solvent in step (2), the mass ratio of triethanolamine, methanol and acetone is 1:3:
4.
5. The method according to claim 1, characterized in that In the step (3), the stirring time is 1 to 3 hours.
6. The method according to claim 1, characterized in that In the step (4), after adding solution 1 to mixed solution 1, the stirring time is continued for 2 to 6 hours.
7. The method according to claim 1, characterized in that In the step (7), the stirring rate is maintained at 300 rpm and the stirring is performed for 10 to 20 minutes.
8. The method according to claim 1, characterized in that In the step (9), the product is washed three times with anhydrous ethanol and then dried; the drying temperature is 60° C. and the drying time is 24 hours.
9. The method according to claim 1, characterized in that: In the step (10), the stirring rate is maintained at 300 rpm and the stirring is carried out for 10 to 20 minutes.
10. The method according to claim 1, characterized in that In the step (12), the product is washed three times with deionized water and then dried; the drying temperature is 80° C. and the drying time is 24 hours.
Citation Information
Patent Citations
Preparation of bifunctional catalyst diatomite domain limited cobalt-platinum-based composite material, and application of bifunctional catalyst diatomite domain limited cobalt-platinum-based composite material in electrocatalytic oxygen reduction reaction and oxygen evolution reaction
CN107342425A
Catalyst and preparation method thereof
CN115970688A
Method of making pyrochlores
CN105026316A
High-conductivity A-bit high-entropy nano metal oxide and preparation method thereof
CN113023777A
Method for preparing high-entropy pyrochlore oxide battery negative electrode material by hydrothermal method
CN115744970A